Seismic Data, Photographic Images and Physical Modeling of Volcanic Plumes as a Tool for Monitoring the Activity of Nevado del Ruiz Volcano, Colombia - Londono, John Makario; Galvis, Beatriz (Frontiers in Earth Science, 2018)
Quantification of volcanic plume parameters is a fundamental task to characterize the behavior of an active volcano. The volcanic plume mass, flow rate and ash injection were determined from seismic data, in addition to photographic images and integration of scaling laws of several volcanic plume models, for the period from 1985 to 2017 for the Nevado del Ruiz Volcano (NRV), Colombia. With these parameters we quantified the ash volume emitted during this period and established a relationship between seismicity and the volcanic plume parameters. The results revealed a decrease of approximately two orders of magnitude in the volume of ash plumes from the November 13, 1985, eruption (0.12 km3) to the September 1, 1989, eruption (1.43 × 10−3 km3). This pattern continued for the June 30, 2012, eruption and 2015–2017 eruptive cycle, with volumes five times smaller than that observed in 1989. The results also exhibited a correlation between the radiated seismic energy (RSE) of the volcanic tremor and ash load for higher (>1 km) and longer-duration (>240 s) plumes. It was possible to calculate a minimum value of ash load based on RSE release and reduced displacement (RD, a means of normalizing volcanic tremors to a common scale) of volcanic tremor signals associated with the eruptions for the period 2015-2017. Moreover, changes in the volume of the ash plume were correlated with changes in the RD and RSE associated with different stages of volcanic activity. These findings can be used as a tool for monitoring the NRV. The continuously decreasing ash plume volumes from 1985 to 2017 suggest a common volcanic cycle that is almost ending. On the other hand, the evidence of new magmatic input in 2007 might suggest that a new volcanic cycle started on that date and is still in the process of ascending magma. It is likely that in the near future surface evidence of the new cycle will be observed at the NRV.